sj-pdf-1-sjp-10.1177_1403494820985172 – Supplemental material for Factors associated with hospitalization, invasive mechanical ventilation treatment and death among all confirmed COVID-19 cases in Norway: Prospective cohort study - Kjetil E. Telle (10009964); Mari Grøsland (9961875); Jon Helgeland (793534); Siri E. Håberg (9291193) (2021)
Supplemental material, sj-pdf-1-sjp-10.1177_1403494820985172 for Factors associated with hospitalization, invasive mechanical ventilation treatment and death among all confirmed COVID-19 cases in Norway: Prospective cohort study by Kjetil E. Telle, Mari GrØSland, Jon Helgeland and Siri E. HÅBerg in Scandinavian Journal of Public Health